An Analysis on Students’ Errors in Writing Sentence Patterns - Nurmala Hendrawati (Loquen, 2018)
Simple, compound, complex, and compound-complex sentences are sentence patterns which each sentence has different pattern, and it is strongly related to grammatical structure, punctuation marks, and connectors. Due to the complexity, EFL learners often get difficulties in understanding and writing the four sentence patterns. Therefore, the objectives of the research are to classify each type of errors and find out the most and least frequently errors of sentence patterns made by students then identify the occurrence frequency of the errors. This is a descriptive qualitative employed by 30 students from the third semester taking Basic Writing, academic year 2017-2018, at Indraprasta PGRI University. This research concerns on surface strategy taxonomy that analyzes four errors. The results show the errors from the highest to the lowest percentage: misformation (57.6%), omission (27.47%), addition (8.8%), and misordering (6.13%). Dealing with sentence patterns, compound-complex sentence becomes the most difficult sentence pattern writing because the most frequently errors made by students are 44.54%. The second is compound sentence with errors 23.2%. Then followed by complex sentence with the number of errors is 22.13%. The least frequently errors of sentence patterns made by students are simple sentence with errors 10.13%. The occurrence of mistake is from the pattern of compound-complex sentence that is the most complicated of three other sentence patterns. The conclusion is regularization in misformation is the most frequently error made by students which cause is from poor understanding of grammatical structure.